Analisis Kebutuhan Pengembangan LKPD Digital Bermuatan Pengalaman Belajar Pembelajaran Mendalam Pada Mata Pelajaran Matematika di Sekolah Dasar - Ni Luh Putu Rani Diana Putri; I Komang Wahyu Wiguna; I Putu Suardipa (Cetta: Jurnal Ilmu Pendidikan, 2026)
This study was motivated by the suboptimal use of Mathematics teaching materials in Grade II elementary schools, which are still dominated by textbooks and simple printed student worksheets. The available teaching materials tend to contain routine exercises, lack interactivity, are not sufficiently contextual, and do not fully provide opportunities for students to understand, apply, and reflect on mathematical concepts in accordance with the characteristics of lower-grade students. This study aimed to analyze Mathematics learning conditions, teacher and student needs, and aspects required in developing digital student worksheets containing Deep Learning Experiences in Grade II of Elementary School Cluster III, Tabanan District, including SDN 1 Dajan Peken, SD Immaculata, SD Saraswati, and SDN 8 Dajan Peken. In this study, Deep Learning does not refer to artificial intelligence technology, but to a pedagogical approach emphasizing learning experiences of understanding, applying, and reflecting. This study was development research focused on the needs analysis stage using a descriptive qualitative approach supported by simple quantitative data. The research subjects consisted of 4 Grade II teachers and 48 Grade II students selected through saturated sampling. Data were collected through observation, interviews, questionnaires, and documentation, then analyzed through data reduction, data display, conclusion drawing, and percentage analysis. The results showed that Mathematics learning was still teacher-centered, media use was not yet optimal, and the worksheets used had not facilitated visual, contextual, interactive, gradual, and reflective learning activities. Teachers needed digital worksheets that were practical, attractive, easy to use, contained contextual problems, and could be accessed through smartphones or laptops. Students needed colorful and illustrated teaching materials with simple instructions, short videos or animations, interactive exercises, immediate feedback, and step-by-step activities. The aspects of digital worksheet development included content, language, appearance, activity presentation, interactivity, technical ease of use, and learning experiences of understanding, applying, and reflecting. Therefore, this study provides an empirical basis for developing Mathematics digital student worksheets that are relevant to the characteristics of lower-grade students and oriented toward active, meaningful, and enjoyable learning experiences.